2011
DOI: 10.1142/s0217979211100035
|View full text |Cite
|
Sign up to set email alerts
|

SIZE-DEPENDENT MAGNETIZATION FLUCTUATIONS IN NiO NANOPARTICLES

Abstract: The finite size and surface roughness effects on the magnetization of NiO nanoparticles is investigated. A large magnetic moment arises for an antiferromagnetic nanoparticle due to these effects. The magnetic moment without the surface roughness has a nonmonotonic and oscillatory dependence on R, the size of the particles, with the amplitude of the fluctuations varying linearly with R. The geometry of the particle also matters a lot in the calculation of the net magnetic moment. An oblate spheroid shape partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…NiO nanoparticles have been characterized by a variety of methods, and they have been shown to possess interesting magnetic, catalytic, and sensing properties. Because of the robust nature of the NiO rocksalt lattice, the particles typically retain the bulk symmetry and stoichiometry over a wide range of sizes and dopant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…NiO nanoparticles have been characterized by a variety of methods, and they have been shown to possess interesting magnetic, catalytic, and sensing properties. Because of the robust nature of the NiO rocksalt lattice, the particles typically retain the bulk symmetry and stoichiometry over a wide range of sizes and dopant concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that, as the crystallite size reduces to the nano-scale, there is an enhancement of the ferromagnetic nature due to the exchange interaction between the uncompensated magnetic surface spins and the antiferromagnetic core spins. 54 The non-zero magnetic moment in a nano-complex is also due to oxygen vacancies. So, first-principle calculations were performed by taking away one O atom from the NiO–Ti complex.…”
Section: Resultsmentioning
confidence: 99%